2013
DOI: 10.1007/s00417-013-2347-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of OCT measurements as prognostic factors in myopic macular hole surgery without foveoschisis

Abstract: Minimum diameter and HFF are strongly correlated with postoperative visual outcomes in cases of MMH. Since analyzing MH configuration seems to improve the anatomical success rate after vitreous surgery in highly myopic patients, these parameters should be preoperatively evaluated by SD-OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…The small size of the macular hole in the current case might be one cause. It has been reported that in both emmetropic and highly myopic eyes, small macular holes were more likely to be closed after surgical treatment [10, 11]. After closure, however, the retinal detachment was reduced with the reabsorption of subretinal fluid by the retinal pigment epithelium (RPE) pump, though this might be inefficient because of the degeneration and atrophy of the RPE and choroid.…”
Section: Resultsmentioning
confidence: 99%
“…The small size of the macular hole in the current case might be one cause. It has been reported that in both emmetropic and highly myopic eyes, small macular holes were more likely to be closed after surgical treatment [10, 11]. After closure, however, the retinal detachment was reduced with the reabsorption of subretinal fluid by the retinal pigment epithelium (RPE) pump, though this might be inefficient because of the degeneration and atrophy of the RPE and choroid.…”
Section: Resultsmentioning
confidence: 99%
“…4-7, 10 Kobayashi et al 6 and Sulkes et al 7 found no association between axial length and anatomical success of surgery. 8,[12][13][14] In an OCT-supported comparative study, Wu and Kung 12 confirmed that the closure rate of myopic macular holes is much lower than in idiopathic cases, 62.5% versus 94.1%. However, Garcia-Arumi et al 4 presented a closure rate of 87.5% and an improvement of visual acuity in 83.3% of the cases.…”
Section: Discussionmentioning
confidence: 95%
“…Despite similar surgical approaches, the anatomical outcome after vitrectomy may be very different from series to series. [25][26][27][28][29] Although it has been shown that longer axial length is associated with more severe traction maculopathy and poorer surgical anatomic outcome, 30 the case number is too small to provide meaningful statistical analysis on risk factors of persistent MH.…”
Section: Discussionmentioning
confidence: 99%